Ruminal parameters and in-situ degradability of rations with wheat middling substitution for corn - Brito, Vinicius Campachi; Silva, Leandro das Dores Ferreira da; Arruda, Maria Carolina Gonçalves de; Tagliatella, Dagiale Kelly de Souza; Grandis, Fernando Augusto; Bumbieris Junior, Valter Harry; Ramos, Lucas Camargo; Camargo, Higor Souza de; Pereira, Vitor Hugo; Mizubuti, Ivone Yurika (Semina: Ciências Agrárias, 2021)
This study aimed to evaluate the effect of substituting corn with wheat middling on the in-situ degradability of foods and ruminal parameters of cattle. The experiment was conducted at the Ruminant Studies Unit and the Laboratory of Food Analysis and Animal Nutrition of Londrina State University. Five rumen-fistulated cattle with an average weight of 521 Â± 38.22 kg were housed in individual stalls. The experimental design used was a Latin square with five treatments (100% C, 75% C 25% WM, 50% C 50% WM, 25% C 75% WM, and 100% WM) and five periods of 25 days each. The pH and ammoniacal nitrogen (N-NH3) concentration in ruminal fluid was measured before feeding and 2, 4, 6, and 8 h after feeding in subdivided parcels. The in-situ degradability of dry matter (DM), organic matter (OM), crude protein (CP), neutral detergent fiber (NDF), and acid detergent fiber (ADF) were determined by incubating silage samples and measuring concentrates in the rumen of cattle. The levels of substitution of corn by wheat middling did not alter the pH and N-NH3 values but was influenced by the collection time. The N-NH3 presented quadratic behavior with a point of maximum rumen concentration (5.31 mgdL-1) reached 1.12 h after feeding. The pH presented quadratic behavior with a point of minimum (6.04) reached 4.32 h after feeding. The effective degradability (ED) of DM with 2, 5 and 8%h-1 of passage rate was influenced by the substitution of corn by wheat middling, with increasing linear behavior. The ED 2%h-1 varied from 46.19% to 50.24%, the ED 5%h-1 varied from 33.76% to 38.68%, and the ED 8%h-1 values ranged from 28.16% to 32.92% for the 100% C and 100% WM treatments. Higher values, for treatments with higher levels of substitution of corn by wheat middling, occurred owing to the lower fiber content and to the largest soluble fractions and degradation rate of DM in rations with wheat middling. The ED of CP and NDF with passage rates of 2, 5 and 8%h-1 presented quadratic behavior. The ED 2, 5 and 8%h-1 of CP presented maximums of 75.9%, 77.9%, and 86.2%, with averages of 52.02%, 45.93%, and 42.23%, respectively. The ED 2, 5 and 8%h-1 of NDF presented minimum points of 29.6%, 34.7%, and 35.2%, with averages of 41.60%, 33.43%, and 27.76%, respectively. Wheat middling can be used for total substitution of corn without damaging ruminal pH and N-NH3, in addition to improving the degradability of rations.